Rebuilding green infrastructure in boreal production forest given future global wood demand. Issue 6 (28th April 2022) - Moor, Helen; Eggers, Jeannette; Fabritius, Henna; Forsell, Nicklas; Henckel, Laura; Bradter, Ute; Mazziotta, Adriano; Nordén, Jenni; Snäll, Tord
Abstract: Global policy for future biodiversity conservation is ultimately implemented at landscape and local scales. In parallel, green infrastructure planning needs to account for socioeconomic dynamics at national and global scales. Progress towards policy goals must, in turn, be evaluated at the landscape scale. Evaluation tools are often environmental quality indicators. How developments of different organism groups will relate to developments of these indicators is unclear. We evaluated three management scenarios for a 100, 000 hectare boreal forest landscape in the coming 100 years in terms of their effects on the future habitat suitability/occupancy of four bird species, six wood‐decaying fungi and one lichen, most of them red‐listed. The scenarios optimize financial returns and account for downscaled projected global demand of wood given a middle‐of‐the road Shared Socioeconomic Pathway (SSP2). We contrast a reference scenario meeting the wood demand against an economy scenario with no upper harvest limit, and a green infrastructure scenario optimizing the levels of environmental indicators. Environmental indicators generally reached the highest and lowest levels in the green infrastructure and economy scenarios, respectively. Most indicators increased further in set‐asides. The profit was 14% lower in the green infrastructure and 2% higher in the economy than in the reference scenario. In the green infrastructure scenario, the species increased on average by 135%, followed by the reference scenario (+65%), and the economy scenario (+47%). All bird species increased in the green infrastructure scenario, while in the other scenarios, only hazel grouse increased and Siberian tit instead decreased. Most fungi increased in the production forest of the green infrastructure scenario but decreased in the economy scenario. All increased in set‐asides. In all scenarios, the lichen Lobaria pulmonaria increased, owing to host tree retention. Synthesis and applications . Effects of global socioeconomic developments can be downscaled and accounted for in planning landscape‐scale forest and conservation management. Accounting for indicators of environmental quality identified forest management scenarios for reaching targets on both revenue and conservation. Rebuilding green infrastructure in the production forest was possible at a relatively minor economic cost and to the benefit of species of conservation concern. Abstract : Effects of global socioeconomic developments can be downscaled and accounted for in planning landscape‐scale forest and conservation management. Accounting for indicators of environmental quality identified forest management scenarios for reaching targets on both revenue and conservation. Rebuilding green infrastructure in the production forest was possible at a relatively minor economic cost and to the benefit of species of conservation concern. Sammanfattning: Global policy för framtida bevarande av biologisk mångfald genomförs i slutändan på landskaps‐ och lokal skala. Parallellt måste planering av grön infrastruktur (GI) ta hänsyn till socioekonomisk dynamik på nationell och global skala. Framsteg mot att nå politiska mål måste i sin tur exekveras på landskapsskala. Indikatorer utgör ofta verktyg för att utvärdera om miljökvalitetsmål (MKM) nås. Hur olika organismgruppers utveckling kommer att förhålla sig till utvecklingen av dessa indikatorer är ofta oklart. Vi utvärderade tre skötselscenarier för ett 100, 000 hektar stort borealt skogslandskap under de kommande 100 åren gällande deras effekter på den framtida utvecklingen av habitatet för förekomst av fyra fågelarter, sex vedsvampar och en lav, de flesta röd‐listade. Scenarierna optimerar den finansiella avkastningen och tar hänsyn till nerskalad, beräknad efterfrågan på virke givet ett globalt medelvägsscenario (SSP2). Vi kontrasterar ett referensscenario som möter virkesefterfrågan mot ett ekonomiscenario utan övre avverkningsnivå och mot ett scenario för grön infrastruktur (GI) som optimerar nivåerna av MKM‐indikatorer. MKM‐indikatorerna nådde i allmänhet de högsta och lägsta nivåerna i GI ‐ respektive ekonomiscenariot . De flesta indikatorerna ökade ytterligare i reservat. Vinsten var 14% lägre i GI‐scenariot och 2% högre i ekonomiscenariot än i referensscenariot . I GI‐scenariot ökade arterna i genomsnitt med 135%, följt av referensscenariot (+65%) och ekonomiscenariot (+47%). Samtliga fågelarter ökade i GI‐scenariot, medan i de andra scenarierna ökade endast järpe, och lappmes minskade istället. De flesta svamparterna ökade i produktionsskogen i GI‐scenariot men minskade i ekonomiscenariot . Alla arter ökade i reservat. I alla scenarier ökade lunglaven ( Lobaria pulmonaria ) på grund av att värdträden sparades som hänsyn. Syntes och tillämpningar . Effekter av globala socioekonomiska framtidsvägar kan skalas ner och nyttjas vid planering av skogsbruk och naturvård på landskapsskala. Genom att ta hänsyn till miljökvalitetsindikatorer identifierades effektivt scenarier som nådde mål för både monetära intäkter och artbevarande. Återuppbyggnaden av den gröna infrastrukturen i produktionsskogen var möjlig till en relativt liten ekonomisk kostnad och gynnade naturvårdsarter.